The Role of Religious Orientation and Defense Mechanisms in the Use of Sexual Pornography - Zahra Pirbonyan; Zahra Nikmanesh; Sana Nourimoghadam (روانشناسی بالینی و شخصیت)
Introduction: The widespread negative effects of pornography, which is an increasingly prevalent issue in today's society, have raised numerous questions regarding the factors that influence the tendency to engage with it. The purpose of this study was to investigate the role of religious orientation and defense mechanisms in the use of pornography among a group of students.Method: The method of the present study was both descriptive and correlational. The statistical population comprised all students at the University of Sistan and Baluchestan. A total of 377 individuals were selected as samples using a multi-stage cluster sampling method. To gather information, we utilized the pornography questionnaires developed by Kerr et al. (2013), the religious self-regulation scale by Ryan et al. (1993), and the defense mechanisms inventory created by Andrews et al. (1993). Data analysis was conducted using Pearson correlation and regression analysis.Results: The findings indicated a significant inverse relationship between the dimensions of introverted and self-accepting religious orientation and sexual pornography. Additionally, there was a significant direct relationship between immature defense mechanisms and sexual pornography. Additionally, the results of the stepwise regression indicated that self-accepting religious orientation and immature defense mechanisms were included in the equation during the first step, explaining 0.13% and 0.02% of the variance in sexual pornography, respectively (p = 0.01).Discussion and conclusion: Religious adherence, attitudes toward pornography, and defense mechanisms play a crucial role in predicting the desire for sexual pornography. Therefore, community health professionals can utilize religious teachings and mature defense mechanisms to develop preventive and therapeutic programs aimed at combating sexual pornography.